Perancangan Branding Candi Palah Penataran Blitar Berbasis Sejarah Sebagai Upaya Meningkatkan Kesadaran Masyarakat - Fanani, Zaenal; Bahruddin, Muh; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
Blitar Regency has a lot of tourism sector, one of which is in the historical Palah Penataran Temple. Palah Penataran Temple is the largest temple complex in East Java and one of the main attractions in Blitar. As a main tourist attraction, promotional activities should be the maximum. This research aims to increase public awareness of historical knowledge about the Palah Penataran Temple. So beside visitors who come to enjoy the beauty of Palah Penataran Temple also understand the historical. Data collection technique is doing by observation, interviews and documentation to obtain the Branding that will be applied to the Palah Penataran Temple. It brings the concept of